2011
DOI: 10.1016/j.jep.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous fraction from Costus spiralis (Jacq.) Roscoe leaf reduces contractility by impairing the calcium inward current in the mammalian myocardium

Abstract: The AqF of C. spiralis leaf depresses myocardial contractility by reducing the L-type calcium current and by decreasing the intracellular calcium transient. Despite the lack of data on the therapeutic dose of AqF used in folk medicine, our results support, at least in part, the traditional use of this plant to treat cardiac disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…It was also demonstrated that the C. spiralis leaves aqueous fraction reduces mammalian myocardium contractility by impairing the calcium inward current in this muscle. This data support the use of C. spiralis in arterial hypertension or cardiac arrhythmias treatment (Britto et al 2011). The antioxidant activity of dichloromethane and methanol extracts of C. spiralis rhizome and root was also demonstrated.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…It was also demonstrated that the C. spiralis leaves aqueous fraction reduces mammalian myocardium contractility by impairing the calcium inward current in this muscle. This data support the use of C. spiralis in arterial hypertension or cardiac arrhythmias treatment (Britto et al 2011). The antioxidant activity of dichloromethane and methanol extracts of C. spiralis rhizome and root was also demonstrated.…”
Section: Introductionsupporting
confidence: 79%
“…It is known that the methanolic extract of C. spiralis leaves presents flavonoids, sterols and alkaloids (Braga et al 2007). The aqueous fraction instead presents phenols, tannins, flavones, xanthones, flavonoids, flavonols, flavononols, flavonones, and saponins (Britto et al 2011). Saponins and flavonol glycosides were isolated from C. spiralis rhizome and leaves, respectively (Antunes et al 2000, Silva andParente 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Damage by A. minuta was sufficiently severe to reduce leaf yield, which is used in medical and pharmacological products (Da Silva & Parente 2004;Silva et al 2008;Quintans et al 2010;Britto et al 2011). Costus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Costus spiralis has tortuous and branched stems, spirally arranged dark green leaves and red, odorless bracts and flowers (Viel et al 1999;Antunes et al 2000). This plant is used to manufacture pharmacological and herbal drugs and has been used in antidiabetic, antirheumatic, diuretic, sudorific and tonic drugs (Da Silva & Parente 2004;Britto et al 2011).…”
Section: Biological and Ecological Consequences Of Diolcogaster Sp (H...mentioning
confidence: 99%
“…3 Menurut penelitian menujukkan bahwa daun pacing mengandung alkaloid, fenol, tanin, flavon, flavonoid, flavonol, dan saponin. 5 Berdasarkan penelitian di India, tumbuhan pacing (Costus spesiosus) dapat digunakan sebagai penyembuhan luka sayat baik bagian daun maupun rimpangnya. 6 Berdasarkan uraian diatas maka perlu dilakukan penelitian terkait aktivitas daun pacing (Costus speciosus) terhadap kesembuhan luka sayat pada kelinci (Oryctolagus cuniculus).…”
unclassified